MAGNETISASI REMANEN BATUAN INTRUSIF DIORIT DARI TRENGGALEK, JAWA TIMUR - Mufit, Fatni
A study of rock magnetism was carried out with 35 diorite samples from Trenggalek East Java This study involved testing the stability of magnetic remanent, identifying magnetic minerals as the carriers of remanent magnetization as well as identifying their grain size. The methods used include alternating field demagnetization, measurement of the IRM (isothermal remanent magnetization) saturation, and the measurement of both low field and anhysteretic susceptibilities. The results showed that the remanent magnetization was unstable as indicated by the drop of magnetic intensity in a relatively low demagnetizing field The direction of remanent magnetization, however, was pretty stable. The remanent magnetization was carried by magnetite (Fe/)4) of 5-25 pan in size. These grains can be categorized as multi-domain (MD). The instability of remanent magnetization is very likely to be caused by the domination of these multi-domain grains of magnetite